PHYTOCHEMICAL EVALUATION OF PUNICA GRANATUM L. LEAF EXTRACT - Sreedevi, P.; Vijayalakshmi, K.; Venkateswari, R. (International Journal of Current Pharmaceutical Research, 2017)
Objective: This study was conducted to assess the phytochemical constituents in Punica granatum L. Leaf extracts (PGLE) using standard methods. Methods: The leaf powder was extracted using solvents namely aqueous, hydroalcohol, ethanol, ethyl acetate and n-hexane. Qualitative and Quantitative phytochemical screenings of PGLE were assessed by standard methods. Results: All the leaf extracts were positive for a wide range of bio-active compounds except n-hexane. The result has showed that the maximum amount of total phenols (394.16 mg/g DW of extract), total tannins (210.5 mg/g DW of extract), flavanoids (147.4 mg/g DW of extract) and total triterpenoids (112 mg/g DW of extract) were noted in ethanolic extract of P. granatum leaf (EPGL). The biological assay revealed that relevant amount of carbohydrate, protein, lipid and alkaloid in EPGL. Conclusion: The findings of this study concluded that the EPGL had potential bioactive substances that may be used as pharmaceutical ingredients for formulation of new or prospective potent drug to cure wide range of metabolic diseases.